OPPORTUNITIES OF ECHOCARDIOGRAPHY IN DIAGNOSTICS OF HEART LESIONS IN CHILDREN WITH SYSTEMIC LUPUS ERYTHEMATOSUS - A.B. Sugak; E.I. Alexeeva; I.V. Dvoryakovskiy (Вопросы современной педиатрии, 2010)
Heart lesions in systemic lupus erythematosus (SLE) are detected in a half of patients, but in most cases it has no clear clinical symptoms and can be revealed only during instrumental diagnostics. 40 children with SLE and 40 conditionally healthy children were examined in this study. The signs of pericardium lesion were detected in 50% of children with SLE, cardiac valves (aortal and mitral) — in 23% of patients, hypertrophy of myocardium of left ventricle — in 33%, dilatation of its camera — in 20%, disorders of diastolic function — in 12,5%, and decrease of contractility of myocardium — in 15%. In total, the signs of myocardium lesions were detected in children and adolescents with SLE more frequently, and valvulitis — rarely than in adults (according to literature data). Revealed differences in heart structure may reflect peculiarities of disease in children and adverse effects of immunosuppressive therapy.Key words: children, systemic lupus erythematosus, echocardiography, pericarditis, myocarditis, endocarditis.(Voprosy sovremennoi pediatrii — Current Pediatrics. – 2010;9(3):43-49)